Mathematics learning organization problems, when we teach children generation Z - Novikienė, Regina (Lietuvos matematikos rinkinys, 2015)
Taking into account the specific features of Z-generation children, the article is the proposed model of learning mathematics and developed problems hindering its realization. The main problems are: lack of students mathematical text reading skills; lack of self-control specifically designed electronic instruments; lack of bright students or programs differentiation.